T. S. Eliot and others: The (more or less) definitive history and origin of the term “objective correlative” - Griffiths, Dominic (My University, 2018)
This paper draws together as many as possible of the clues and pieces of the puzzle surrounding T. S. Eliot’s “infamous” literary term “objective correlative”. Many different scholars have claimed many different sources for the term, in Pound, Whitman, Baudelaire, Washington Allston, Santayana, Husserl, Nietzsche, Newman, Walter Pater, Coleridge, Russell, Bradley, Bergson, Bosanquet, Schopenhauer and Arnold. This paper aims to rewrite this list by surveying those individuals who, in different ways, either offer the truest claim to being the source of the term, or contributed the most to Eliot’s development of it: Allston, Husserl, Bradley and Bergson. What the paper will argue is that Eliot’s possible inspiration for the term is more indebted to the idealist tradition, and Bergson’s aesthetic development of it, than to the phenomenology of Husserl.
Keywords: Eliot, T.S.; Objective correlative (phrase)